(untitled) (Global Journal of Human-Social Science, 2024)
The literature on national plans to reduce emissions from deforestation and forest degradation REDD shows that the stakeholders present in the territory especially the communities are the focus of these actions The article questions the level of community engagement in a proposed REDD project in the Amazon by private companies with the aim of analyzing the socio-economic and environmental aspects of community residents The theoretical framework integrates stakeholder theory and community participation theory to support the analysis of the level of engagement 338 small rural producers were chosen from among the residents of 23 communities in four municipalities in the state of Par The sociodemographic characteristics were collected and structured in tables and graphs The results reveal that the communities are socially disjointed with problems defining property rights and access to government goods and services which makes it difficult to achieve the benefits declared by the REDD project